2009
DOI: 10.1007/s10295-009-0576-1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-scale biofiltration of acrylonitrile by Rhodococcus rhodochrous DAP 96622 in a trickling bed bioreactor

Abstract: Acrylonitrile (ACN), a volatile component of the waste generated during the production of acrylamide, also is often associated with aromatic contaminants such as toluene and styrene. Biofiltration, considered an effective technique for the treatment of volatile hydrocarbons, has not been used to treat volatile nitriles. An experimental laboratory-scale trickling bed bioreactor using cells of Rhodococcus rhodochrous DAP 96622 supported on granular activated carbon (GAC) was developed and evaluated to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…have also been observed in granular activated carbon to remove acrylamide in a laboratory scale trickling filter bioreactors by Zhang and Pierce. 59 TDR also supported the growth of Aquabacterium , Stenotrophomonas , Rhizobacter and Erythromicrobium (Fig. 7a).…”
Section: Resultsmentioning
confidence: 66%
“…have also been observed in granular activated carbon to remove acrylamide in a laboratory scale trickling filter bioreactors by Zhang and Pierce. 59 TDR also supported the growth of Aquabacterium , Stenotrophomonas , Rhizobacter and Erythromicrobium (Fig. 7a).…”
Section: Resultsmentioning
confidence: 66%
“…This volatile organic compound (VOC) is detected as an in-door air component emitted by commercial fibrous polymeric materials, resins and smoking tobacco [2,3]. Traditional VOCs control technologies include adsorption [4], thermal incineration at temperatures of 1000-1200°C, catalytic incineration at temperatures of 250-500°C [5][6][7] and bio-filtration [8][9][10] suffering from high operating costs, secondary waste stream problems and narrow range of working conditions (bio-filtration).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Pierce [ 14 ] have also used the bacterium Rhodococcus to degrade VOCs and the results of their research have shown a treatment efficiency of about 90%. Italian and Tunisian scientists also used the bacterium Rhodococcus for VOC removal.…”
Section: Introductionmentioning
confidence: 99%